Answer:
→ 4. ![2(3x-2y)](https://tex.z-dn.net/?f=2%283x-2y%29)
→ 3. ![2(3-2x)](https://tex.z-dn.net/?f=2%283-2x%29)
→ 1.
→ 2.
Step-by-step explanation:
You need to:
Factor out 2 from
, then you get the equivalent expression:
this matches with OPTION 4
Factor out 2 from
, then you get the equivalent expression:
this matches with OPTION 3
Make the subtraction for
, then you get the equivalent expression:
this matches with OPTION 1
Factor out 2 from
, then you get the equivalent expression:
this matches with OPTION 2
Answer:
B) exactly one solution
Step-by-step explanation:
Based on the particular equation the answer should be 3
Step 1 is the correct answer because to begin solving you must add 1 to both sides of the equation